2012
DOI: 10.3389/fendo.2012.00003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Starvation on Brain Short Neuropeptide F-1, -2, and -3 Levels and Short Neuropeptide F Receptor Expression Levels of the Silkworm, Bombyx mori

Abstract: In our previous report, we demonstrated the possibility that various regulatory neuropeptides influence feeding behavior in the silkworm, Bombyx mori. Among these feeding-related neuropeptides, short neuropeptide F (sNPF) exhibited feeding-accelerating activity when injected into B. mori larvae. Like other insect sNPFs, the deduced amino acid sequence of the cDNA encoding the sNPF precursor appears to produce multiple sNPF and sNPF-related peptides in B. mori. The presence of three sNPFs, sNPF-1, sNPF-2, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
34
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 48 publications
6
34
0
1
Order By: Relevance
“…However, the sample of NEUTRAL-cells here was relatively small, and we not record from raphe pallidus, a subregion of the RVM and known target of PB efferents, which has a well-documented role in thermoregulation. 54 …”
Section: Discussionmentioning
confidence: 99%
“…However, the sample of NEUTRAL-cells here was relatively small, and we not record from raphe pallidus, a subregion of the RVM and known target of PB efferents, which has a well-documented role in thermoregulation. 54 …”
Section: Discussionmentioning
confidence: 99%
“…The functions of these peptides were found to be similar to those of vertebrate NPYs [14]. In the silk worm, Bombyx, it has been suggested that sNPF regulates hormone release and regulate JH synthesis along with allatotropin [15,16]. In the locust, it affected the synthesis of vitellogenin via juvenile hormone (JH) synthesis [17] and stimulated ovarian development [6,18].…”
Section: Introductionmentioning
confidence: 96%
“…This may also be the case in the locust, in which an injection of sNPF may have indirectly affected the synthesis of vitellogenin via juvenile hormone (JH) synthesis (Schoofs et al 2001). In B. mori, sNPF has been shown to regulate JH synthesis along with allatotropin (Nagata et al 2012). sNPF has also been implicated in the regulation of feeding behavior in D. melanogaster (Garczynski et al 2006).…”
Section: Introductionmentioning
confidence: 99%